Effective notch stress method for fatigue assessment of sheet alloy material and bi-material welded joints. (June 2020) - Chang, Yufang; Sun, Chaojie; Qiu, Yu
Abstract: As notch stress can effectively reflect the influence of welding geometry on local stress concentration, it can be used for fatigue strength evaluation of complex welded joints. In order to avoid stress singularity effect caused by the corner, virtual radius is introduced into fatigue evaluation of welded structures. However, the virtual radius recommended by the current specifications is only for steel and aluminum alloy materials, and is not applicable for thin-plate structures, especially for welded structures of special alloy materials and dissimilar materials. Considering the influence of alloy materials and size effect on hypothetical virtual notch stress, based on effective notch stress theory and finite element method, the optimal virtual radius values suitable for thin-plate alloy welded structures are proposed and verified respectively. After optimizing the virtual radius, the scatter band index of the notch stress S–N curve is significantly lower than the result of nominal stress. Highlights: Effective notch stress method was adopted for the evaluation of notch stress and fatigue strength of sheet alloy materials. The optimal virtual radius values for magnesium alloy welding structure and aluminum-steel welded structure are proposed. Based on experimental data, the optimal virtual radius values suitable for thin-plate alloy welded structures are verified.